Enhanced Peelability and Quality of Whiteleg Shrimp (Litopenaeus vannamei) Using Pulsed Electric Field (PEF) Treatment - Gyeong-Seo Park; Hyeon Seo; Han-Baek Lee; Ji-Won Lee; Hafiz Muhammad Shahbaz; Se-Ho Jeong; Dong-Un Lee (Foods)
This study investigated the effects of pulsed electric field (PEF) treatment on the peeling efficiency and textural properties of whiteleg shrimp (Litopenaeus vannamei). Shrimp samples were treated at field strengths of 0, 1.0, 1.5, and 2.0 kV/cm to assess PEF impact on peeling force, incomplete peeling percentage, and texture profile. The results showed that PEF treatment significantly reduced the peeling force from 50.88 N in controls to 42.99 N at 2.0 kV/cm, while the percentage of incompletely peeled shrimp decreased from 27.5% to 15.9%. Texture profile analysis indicated that PEF treatment had no impact on the key properties of hardness and chewiness (no significant difference), with a reduction in springiness observed at higher field strengths. Improvements in peelability are attributed to electroporation, which disrupts collagen in the connective tissue between the shrimp shell and muscle. These findings indicate that PEF treatment is an efficient, non-thermal method for enhancing shrimp peeling processes while preserving textural integrity. PEF technology offers a promising alternative to traditional mechanical and thermal methods in the seafood processing industry.